2019
DOI: 10.1111/bjhp.12390
|View full text |Cite
|
Sign up to set email alerts
|

Fighting the flinch: Experimentally induced compassion makes a difference in health care providers

Abstract: Objectives. Although health care providers are required to sustain care in difficult circumstances, some patients challenge this principle. Evoking compassion seems likely to be helpful in such situations. This research aimed to evaluate whether inducing compassion in health care providers might mitigate disengagement with patients who have challenging presenting features such as those with disgusting symptoms and/or are to blame for their own health problems.Design. An online experimental study with clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“… 146 A 2-minute compassion condition slideshow consisting of images of humans or animals in various situations depicting helplessness, vulnerability, and physical and emotional pain induced clinical engagement and compassion in qualified health professionals. 147 Evaluation methods for these programs were varied (see Table 1 and Supplemental Digital Appendix 3 at http://links.lww.com/ACADMED/B91 for more information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 146 A 2-minute compassion condition slideshow consisting of images of humans or animals in various situations depicting helplessness, vulnerability, and physical and emotional pain induced clinical engagement and compassion in qualified health professionals. 147 Evaluation methods for these programs were varied (see Table 1 and Supplemental Digital Appendix 3 at http://links.lww.com/ACADMED/B91 for more information).…”
Section: Resultsmentioning
confidence: 99%
“…A limited number of studies in this systematic review included a comparator/control group in the assessment of the impact of the compassion education intervention. 45 , 47 , 48 , 51 53 , 56 , 109 , 118 , 125 , 127 , 135 , 138 , 147 The majority of studies identified used only a single group post-test design to evaluate the intervention, with the lack of a comparator/control group hindering our ability to determine whether a given intervention increased, decreased, or did not change learners’ compassion as compared with what they possessed at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this view, basic science work tells us that "compassion fade" is moderated by dispositional factors (Markowitz et al, 2013) and that the extent to which suffering is self-inflicted (Reynolds et al, 2019) and that greater self-other similarity are likely important (Oveis et al, 2010). More directly, experimental studies in health contexts have shown that compassion and patient engagement are more impacted by aversive patient characteristics among student physicians than among more experienced practitioners (Reynolds et al, 2019). Although developmental effects were not evident in the data presented here, individual differences in the tendency or ability to use particular types of compassion-maintaining strategies may well help us understand responses to the array of challenges to compassion evident in healthcare settings.…”
Section: Characterizing the Range Of Compassion-maintaining Strategiesmentioning
confidence: 95%
“…The Transactional Model (Fernando and Consedine, 2014a) suggests that compassion arises out of the dynamic interactions between patient, clinician, the clinical picture, and the environments in which compassion is needed. Consistent with this view, basic science work tells us that "compassion fade" is moderated by dispositional factors (Markowitz et al, 2013) and that the extent to which suffering is self-inflicted (Reynolds et al, 2019) and that greater self-other similarity are likely important (Oveis et al, 2010). More directly, experimental studies in health contexts have shown that compassion and patient engagement are more impacted by aversive patient characteristics among student physicians than among more experienced practitioners (Reynolds et al, 2019).…”
Section: Characterizing the Range Of Compassion-maintaining Strategiesmentioning
confidence: 97%
See 1 more Smart Citation